THE PROFESSIONAL ACCOUNTING EDUCATION PROVISION OF HIGHER EDUCATION INSTITUTIONS IN THAILAND FOR FREE MOBILITY OF EDUCATED LABOUR IN ACCOUNTANCY SERVICES SUPPORTING TO ASEAN COMMUNITY - ผลแก้ว, ชัยมงคล; ดำพิทักษ์, กุสุมา; วัชรสินธุ, สายจิต; มูลเมือง, กิ่งกาญจน์; เตรียมมีฤทธิ์, นภาพร (RMUTT Global Business and Economics Review, 2017)
This research aims to investigate the operating mechanism of Thai public and private universities for preparing students to compete in ASEAN Economic Community (AEC). Significant problems in the development of competitive advantages for Thai accountants are included in this research. An in-depth interview was used for data collecting by deans or heads of accounting department of 30 universities in the middle region of Thailand. Research findings present significant operating mechanism that Thai universities used to prepare students for AEC. The mechanism consists of 1) the development of cooperative among universities, budgeting allocation for the development of academics and learning facilities; 2) the development of accounting curriculum based on Thai Qualifications Framework for Higher Education, International Education Standards, Internship/Co-operative Education, and Accounting Accreditation; 3) the development of teaching and learning methods by including a variety of teaching techniques, English and ASEAN language, and professional ethics; 4) organizing extra-curriculum activities; 5) establishing co-operative with business entrepreneurs for the development of accounting profession for students. Significant problems in preparing Thai students to compete in AEC are communications and technology skills. Understanding the operating mechanism and problems in preparing students to AEC would be an important guideline for universities to improve their teaching and learning systems for future competitive advantage.